Girl-child Sexual Violence and Academic Achievement in Public Primary Schools of Kuria West Sub-County, Kenya - (Sr) and Kenneth Otieno., Sussy Nafula Werunga (International Journal of Scientific Research and Management (IJSRM), 2016)
The study sought to examine girl-child sexual violence and academic achievement in public primary schools of Kuria West Sub-county. Despite Mechanisms put in place by Ministry of Education to gab girl child sexual violence in Schools, home factors such as Female Genital Mutilation and developed relationships between boys and girls in school contribute significantly to sexual violence among girls. It affects girls’ completion of education and disrupts their career potential since many of them drop out of school because of the unwanted pregnancy. Although Kenya’s MOEST’s health policy (2009) allows girls who conceive to resume their studies after delivery, girls drop out because of the shame and trauma. Guidance and counseling teachers ought to provide psychosocial support to girls to overcome shame and trauma. However there is laxity in some of the schools where guidance and counseling services have not addressed girls’ sexual violence hence high dropout rate. The study was carried out in 28 public primary schools and the sub-county education office. The sample size consisted of 360 girls of class 7 and 8, 27 Head teachers, 27 Guidance and counseling teachers and 1 Education officer. Stratified, simple random and saturated sampling techniques were employed. Questionnaires, interview schedules and document analysis guide were used to collect data. Data was analyzed using Statistical Package of Social Science (SPSS) version 18. Quantitative data was presented using descriptive statistics. Female Genital Mutilation was the most contributing home factor that makes girls concentrates on sexual activities. The least factor was fathers raping girls at home. Girls abused sexually due to developed relationships with boys and teachers for the exchange of grades were the most and least school factors respectfully. It was recommended that; the community should use alternative initiation rite of passage for girls instead of female genital mutilation to educate girls on cultural matters; head teachers should strengthen school rules, regulations and counseling programme to guide pupils; the Ministry of education should organize sensitization workshops for parents, Board of Management and head teachers on legal handling of sexual violence and Teachers Service Commission should employ more effective ways of disciplining teachers involved in sexual abuse in schools.